PUTUSAN NOMOR 465K/PDT.SUS-HKI/2023 TENTANG PENGGUNAAN ALAT BUKTI PADA SENGKETA MEREK: Decision Number 465K/Pdt.Sus-HKI/2023 Concerning the Use of Evidence in Trademark Disputes - Tias Pinky Ananda; Goeltom, Elfrida Ratnawati (Faculty of Law, Universitas Trisakti, 2025)
This study aims to examine the legal reasoning in Supreme Court Decision Number 465K/Pdt.Sus-HKI/2023 concerning the use of evidence in a trademark dispute. The main focus is to assess whether the evidentiary process aligns with the provisions of the Indonesian Civil Procedure Code (HIR/RBG), and to analyze the legal consequences of trademark protection granted to the prevailing party in cases where the judicial reasoning does not fully satisfy the procedural standards of evidence. This normative juridical research employs a qualitative approach, utilizing both primary and secondary legal sources analyzed descriptively. The identification of the issue in this study lies in the procedural inadequacy of trademark certificates submitted as legal evidence. Based on the findings and conclusion, it is concluded that in Decision Number 465K/Pdt.Sus-HKI/2023, Mohindar H.B, as the registered trademark holder of Number 173934